Invasive papillary carcinoma of the breast - Wang, Shijing; Zhang, Qingfu; Mao, Xiaoyun (Frontiers in Oncology, 2024)
Invasive papillary carcinoma is a rare form of breast cancer that is more likely to occur in postmenopausal women. Previous studies have been limited to case reports and small retrospective studies, leading to low awareness of this type of tumor and difficult clinical management. According to the available literature, invasive papillary carcinoma exhibits unique pathological features and biological behavior. Invasive papillary carcinoma is mostly luminal, with a low rate of lymph node metastasis, which underlies its favourable prognosis. The effectiveness of adjuvant therapy in reducing tumour burden and improving prognosis in patients with invasive papillary carcinoma remains uncertain. Due to the rarity of the lesion, conducting prospective clinical trials is impractical. The use of biological models, such as organoids, can help alleviate the impact of the scarcity of this condition on research. In addition, invasive papillary carcinoma is affected by specific genomic events, and more extensive studies of gene expression profiling may provide molecular-level insights to make optimal therapeutic decisions.